Puerarin ameliorates non-alcoholic fatty liver disease by inhibiting lipid metabolism through FMO5 - Li, Zhaoyi; Cao, Wenjing; Zhang, Yuxuan; Lai, Shanglei; Ye, Yingyan; Bao, Jianfeng; Fu, Ai (Frontiers in Pharmacology, 2024)
Pueraria lobata is traditionally used in China for treatment of non-alcoholic fatty liver disease (NAFLD). Puerarin, a functional drug extracted from Pueraria lobata, features a pharmacological activity. The present study aims to investigate the effect of puerarin intervention on NAFLD. We established an NAFLD mouse model using a high-fat diet with 60% fat and evaluated the impact of puerarin intervention. Our results demonstrate that puerarin intervention significantly ameliorates lipid accumulation and protects the liver from high-fat-induced damage while reducing oxidative stress levels in the liver. Furthermore, puerarin intervention significantly downregulates the transcription levels of acetyl-CoA carboxylase (ACC1) in the liver. It also upregulates the transcription levels of carnitine palmitoyltransferase 1(CPT1), peroxisome proliferator-activated receptor alpha (PPARα), and peroxisome proliferators-activated receptor γ coactivator alpha (PGC1α), which are related to oxidation. Furthermore, we demonstrated that flavin-containing monooxygenase (FMO5) was involved in the protective effect of puerarin against NFALD. In conclusion, the present study demonstrated the beneficial effect of puerarin on NAFLD and showed that puerarin could prevent liver injury and lipid accumulation caused by NAFLD via activating FMO5. These findings provide a new theoretical basis for applying puerarin as a therapeutic agent for NAFLD.